2014
DOI: 10.1186/1756-3305-7-278
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and photoperiod on daily activity rhythms of Lutzomyia longipalpis (Diptera: Psychodidae)

Abstract: BackgroundInsect vectors have been established as models in Chronobiology for many decades, and recent studies have demonstrated a close relationship between the circadian clock machinery, daily rhythms of activity and vectorial capacity. Lutzomyia longipalpis, the primary vector of Leishmania (Leishmania) infantum in the New World, is reported to have crepuscular/nocturnal activity in the wild. However, most of these studies applied hourly CDC trap captures, which is a good indicative of L. longipalpis behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 27 publications
2
19
0
4
Order By: Relevance
“…The explanation for this could be the fact that seasonal dynamics is a complex process resulting from abiotic variables modulating biotic ones. Temperature, rainfall, and RH have previously been studied as possible factors associated with phlebotomine seasonal dynamics (Oliveira et al, 2008, Zeilhofer et al, 2008de Oliveira et al, 2013;de Andrade et al, 2014), as well as photoperiod (Rivas et al, 2014). However, climatic variables not only have effects on current activity and therefore the success of trapping, but also have delayed effects mediated by breeding site availability and population size-cohort progression (Salomón et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The explanation for this could be the fact that seasonal dynamics is a complex process resulting from abiotic variables modulating biotic ones. Temperature, rainfall, and RH have previously been studied as possible factors associated with phlebotomine seasonal dynamics (Oliveira et al, 2008, Zeilhofer et al, 2008de Oliveira et al, 2013;de Andrade et al, 2014), as well as photoperiod (Rivas et al, 2014). However, climatic variables not only have effects on current activity and therefore the success of trapping, but also have delayed effects mediated by breeding site availability and population size-cohort progression (Salomón et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Lutzomyia longipalpis and Ny. whitmani show spatial and temporal variations in their abundances (Brandão-Filho et al, 2011;Donalisio et al, 2012;Fernández et al, 2012Fernández et al, , 2013, and there are also studies of the distribution of these species at the village/city spatial scale (Oliveira et al, 2008;de Souza et al, 2014). However, studies simultaneously examining the seasonal−village abundance distributions of both species, with a focus on TL/VL, are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, o aumento da temperatura também aumenta a densidade de flebotomíneos adultos e, por sua vez, o contato entre vetor e hospedeiros e consequentemente a disseminação da doença 16,17 . Corroborando isso, a temperatura pode aumentar a atividade dos flebotomíneos 18 , e repastos sanguíneos repetidos elevam a carga parasitária no vetor 19 , aumentando, dessa forma, a infectividade dos flebotomíneos.…”
Section: • Autocorrelação Espacial Global E Local Bivariadaunclassified
“…Ao que parece, não seriam nem temperaturas muito elevadas e nem tão baixas, associadas à ocorrência da LV neste estado 26 , pois assim como se cita a relação da temperatura com a reprodução do parasito, esta também influencia a atividade vetorial. A L. longipalpis apresenta tendência a ser mais ativa à noite, em temperatura de 30ºC 18 , que coincide com as baixas temperaturas diurnas identificadas neste estudo. Os flebotomíneos são vulneráveis a mudanças bruscas de temperatura e, geralmente, preferem regiões nas quais ocorre baixa variação entre as temperaturas mínimas e máximas, visto que sua sobrevivência pode ser reduzida se o clima ficar muito quente e seco 16,27 e, dessa maneira, temperaturas altas diminuem também os casos de LV humana 26 .…”
Section: Evi: íNdice De Vegetação Melhorado (Enhanced Vegetation Index)unclassified
“…Thus, the exposure of individuals -hosts and reservoir -to the vectors can be increased. Rivas et al (23) showed that at 30ºC, the maximum peak of the abundance of Lu. longipalpis was considered lower than the other lower temperature regimes (20ºC and 25ºC).…”
Section: Discussionmentioning
confidence: 99%